Enhanced thermoelectric properties of highly conductive poly (3,4-ethylenedioxy thiophene)/exfoliated graphitic carbon nitride composites - Ugraskan, Volkan; Karaman, Ferdane (ELSEVIER SCIENCE SA, 2022)
In this study, the thermoelectric properties of as-synthesized and -exfoliated graphitic carbon nitride (g-C3N4) filled poly (3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT: PSS) were investigated. Firstly, g-C3N4 was synthesized by heating of guanidine-HCl at 550 ?& nbsp;and exfoliated using an ultrasonic homogenizer. Then, PEDOT:PSS was synthesized by oxidative chemical polymerization. Finally, the composites containing different weight ratios of g-C3N4 were prepared. The conductivity of pristine PEDOT:PSS increased from 11.1 Scm(-1) to 722.15 Scm(-1) for the composite containing 25% exfoliated g-C3N4, whereas the power factor of PEDOT: PSS increased from 0.19 mu Wm(-1)K(-2) to 419.7 mu Wm- 1K-2 for the composite containing 15% exfoliated g-C3N4. This study suggests that exfoliated g-C3N4 is a promising material to increase the electrical conductivity and power factor of PEDOT:PSS.
Keywords: Thermoelectric; PEDOT: PSS; Graphitic carbon nitride; EFFICIENT PHOTOCATALYSTS; SEEBECK COEFFICIENTS; GRAPHENE; PEDOTPSS; NANOSHEETS; PERFORMANCE; FABRICATION; ENERGY; BLACK; FILMS; Materials Science; Physics; Polymer Science